Analiza primanjkljaja odtoka po metodi praga na primeru treh vodomernih postaj v Sloveniji - Cunja, Jan (Acta hydrotechnica, 2020)
This analysis deals with the comparison of volume and duration of runoff deficits using different drought thresholds for the gauging stations Polana on the Ledava, Litija on the Sava, and Kubed on the Rižana Rivers with different climatic conditions for the hydrologically driest years in the period 1960-2016 in Slovenia. Using the threshold method, all events in which discharge fell below a pre-selected threshold value were identified as drought events. Three different values were chosen for the threshold value, namely the mean low periodic discharge sQnp and the percentiles of flow duration curve Q90 and Q80. For each gauging station, the event with the largest deficit volume and duration, as well as the total annual deficit volume and the total duration of drought events for the individual year, were selected using different threshold values. The studys results demonstrate that the choice of drought threshold can have a great impact on the results of runoff deficit analyses. The absolute values of the duration and volume of the runoff deficits increase with higher threshold values. Also the ratios between the results of the individual years change slightly when the threshold value changes. Regardless of the choice of the threshold, 2003 proved to be the driest year according to all four selected drought characteristics and for all three analysed gauging stations, followed by 1993, 1971, and 2012, respectively. However, drought is a specific phenomenon of a regional character and is reflected differently in the different regions of Slovenia.
Keywords: hidrološka suša; hydrological drought; hydrology; metoda praga; primanjkljaj odtoka; runoff deficit; Slovenia; Slovenija; treshold method